Find the sum to 50 terms of the summation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I could find out that the series went something like this:
1 × 2 1 ( 1 + 1 ) + 2 × 2 2 ( 2 + 1 ) + 3 × 2 3 ( 3 + 1 ) + …
So, by inference, we can realize that the n t h term (denoted here by t n ) is:
t n = n × 2 n ( n + 1 )
We need to find
n = 1 ∑ 5 0 2 n 3 + n 2 = S
⇒ S = n = 1 ∑ 5 0 2 n 3 + n = 1 ∑ 5 0 2 n 2
⇒ 2 S = ( 2 5 0 × 5 1 ) 2 + 6 5 0 × 5 1 × 1 0 1 = 1 6 2 5 6 2 5 + 4 2 9 2 5 = 1 6 6 8 5 5 0
⇒ S = 2 1 6 6 8 5 5 0 = 8 3 4 2 7 5